Menjamin Hak Perempuan dengan Taklik Talak dan Perjanjian Perkawinan - Khoiruddin Nasution (Unisia, 2008)
The concepts of taklik talak and/or marital agreement have been recognized in Indonesiafor long time. However, those who are knowledgeable of them are still limited to certainpeople. Since the first time until their appearance in the Marriage Law and regulations, thetaklik talak and/or marital agreement have been intended to guarantee the rights of wivesand to protect them from discriminative and arbitrary actions of husbands. Despite theirlong existence, the concepts have not been fully conceived by society in general. Thislack of understanding of the concepts has been caused by lack of socialization, andtherefore, the socialization should be continuously and substantially done.Keywords: marital agreement, wives, discriminative and arbitrary, socialization.